Phosphate (Pi) uptake and remobilisation within plant in Brassica spp. under different Pi availabilities input. Issue 1 (April 2021) - Shahbuddin, D; Goodall, A; Hammond, J P
Abstract: Phosphorus (P) is one of six essential macronutrients in plants to ensure crop growth and productivity. Plants only acquire phosphorus in the form of inorganic phosphate (Pi) known as orthophosphate, mainly in the form of H2 PO4 − . The high demand of Pi in fertilisers for agriculture use contributed to environmental pollution. Therefore, it is important to understand the Pi uptake from the soil and remobilisation within the plant to increase P use efficiency (PUE). In this study, the experiments were undertaken to look at the variation of Pi uptake by Brassica spp. under different soil Pi availability. Two soil Pi concentrations, P1 (0 g L −1 ) and P4 (0.225 g L −1 ) were selected to represent the low and high Pi treatment, respectively. B. napus plants grown in compost with both high and low Pi treatments were harvested at four different parts of the plant (leaf, stem, flower, and pod silique and seed) at six different growth stages, namely two-leaf stage, four-leaf stage, flowering stage, first flower opens stage, seed filling stage and maturity stage. The results of free Pi concentration in P4 (0.225 g L −1 ) were significantly higher than P1 (0 g L −1 ) (P ≤ 0.01). Remobilisation of Pi determined by total P contents of plants treated with P1 and P4 both showed similar trends, increased P contents up to 50% of plant P at harvest 5 (seed stage), and loss of P at leaf, stem and flower tissues during senescence at maturity stage. Under deficiency, leaf Pi concentration which determined the internal Pi redistribution showed Pi was redistributed from source (mature organs) to sink (developing tissues) Pi tissues. These results provide insights on plant nutrient status and can be used for further investigation for crop optimal production under low Pi availability.